Decoración de la peluqueria Mennen ubicada en las calles sucre entre 10 de agosto y rocafuerte en la ciudad de Loja - Alvarado Zumba, José Daniel (2015)
The project present entitled “DESIGN OF BARBERSHOP MENNEN” trade about of design space so that is basic in the image of the barbershop and the impact before the client, is by is that the work present embrace your origin, history, measure, accesory, decoration of elements, the aspects sociality- cultures, economic and the fuctions de barbershop.